Speleothems reveal 500,000-year history of Siberian permafrost - Vaks, A; Gutareva, O; Breitenbach, S; Avirmed, E; Mason, A; Thomas, A; Osinzev, A; Kononov, A; Henderson, G (American Association for the Advancement of Science, 2013)
Soils in permafrost regions contain twice as much carbon as the atmosphere, and permafrost has an important influence on the natural and built environment at high northern latitudes. The response of permafrost to warming climate is uncertain and occurs on time scales longer than those assessed by direct observation. We dated periods of speleothem growth in a north-south transect of caves in Siberia to reconstruct the history of permafrost in past climate states. Speleothem growth is restricted to full interglacial conditions in all studied caves. In the northernmost cave (at 60°N), no growth has occurred since Marine Isotopic Stage (MIS) 11. Growth at that time indicates that global climates only slightly warmer than today are sufficient to thaw extensive regions of permafrost.